Overexpression of a cytochrome P450 and a UDP-glycosyltransferase is associated with imidacloprid resistance in the Colorado potato beetle, Leptinotarsa decemlineata - Emine Kaplanoglu; Patrick Chapman; Ian M. Scott; Cam Donly (Scientific Reports, 2017)
Abstract Current control of insect pests relies on chemical insecticides, however, insecticide resistance development by pests is a growing concern in pest management. The main mechanisms for insecticide resistance typically involve elevated activity of detoxifying enzymes and xenobiotic transporters that break-down and excrete insecticide molecules. In this study, we investigated the molecular mechanisms of imidacloprid resistance in the Colorado potato beetle, Leptinotarsa decemlineata (Say) (Coleoptera: Chrysomelidae), an insect pest notorious for its capacity to develop insecticide resistance rapidly. We compared the transcriptome profiles of imidacloprid-resistant and sensitive beetle strains and identified 102 differentially expressed transcripts encoding detoxifying enzymes and xenobiotic transporters. Of these, 74 were up-regulated and 28 were down-regulated in the resistant strain. We then used RNA interference to knock down the transcript levels of seven up-regulated genes in the resistant beetles. Ingestion of double-stranded RNA successfully knocked down the expression of the genes for three cytochrome P450s (CYP6BQ15, CYP4Q3 and CYP4Q7), one ATP binding cassette (ABC) transporter (ABC-G), one esterase (EST1), and two UDP-glycosyltransferases (UGT1 and UGT2). Further, we demonstrated that silencing of CYP4Q3 and UGT2 significantly increased susceptibility of resistant beetles to imidacloprid, indicating that overexpression of these two genes contributes to imidacloprid resistance in this resistant strain.